De sanctis-cacchione syndrome with subdural effusion: A rare case from india with review of literature - Aritra Kapat; Gourab Roy; Angana Bhattacharjee; Asok K Mandal; Ashok K Bala; Indrashis Podder (Wolters Kluwer Medknow Publications, 2023)
De Sanctis-Cacchione syndrome (DCS) formerly known as xerodermic idiocy is characterised by cutaneous photosensitivity, microcephaly, mental retardation, short stature, hypogonadism, spasticity, peripheral neuropathy and sensorineural deafness. Here in, we present the case of a four and half years old male child with features of severe acute malnutrition (SAM) with a typical bird like facies and sunken eyes who had history of photosensitive pruritic pigmentary skin lesions on sun exposed areas from a very early age of six months. Gross developmental delay, ataxia, microcephaly, short stature, hypogonadism and cachectic wasting were identified on examination and hypertransaminasemia and hypothyroidism were recorded from biochemical profile. Subsequent visual evoked response and brainstem evoked response audiometry revealed anterior visual pathway dysfunction and bilateral profound sensorineural hearing loss. Magnetic resonance imaging of brain yielded subdural effusion with mass effect in addition to cerebro-cerebral atrophy and demyelination. Skin biopsy further detected dysplastic changes and early signs of squamous cell carcinoma (SCC). Although few cases are reported sporadically throughout the world, to our best of knowledge till date only 11 such cases have been reported completely in Indian medical literature which makes our case report the 12th one with distinctive novel association of subdural effusion.